The punishment of violence against children is reviewed from the perspective of the purpose of punishment - Yani Brilyani Tavipah (LEGAL BRIEF, 2024)
Violence against children is a criminal act that needs attention currently in Indonesia. Cases of violence against children, especially sexual violence, are quite high and the perpetrators are people close to them or even family members, requiring harsher criminal measures through the Child Protection Law. It is hoped that imposing high or serious penalties in resolving cases of violence against children can reduce the occurrence of violence against children in the future. The type of research used in this writing is analytical descriptive, by describing the problem of violence against children that occurs in Indonesia and then analyzing it based on relevant theories. The data used is secondary data; The data collection technique is carried out by searching for online data. The conclusion of this research is that the application of the Child Protection Law in resolving cases of violence against children by imposing heavy penalties has a strong basis, that punishment brings goodness, prevents worse incidents, and there is no other alternative for perpetrators of violence against children other than However, the imposition of serious criminal penalties is an effort to reduce the occurrence of criminal acts of violence against children. So far this has not been successful in reducing the current rate of violence against children, other efforts are needed that can support the realization of the objectives of this punishment